Vaccine Hesitancy Affecting Pneumococcal Vaccine Refusal in Older Adults with Morbidities - Woothikrai Chitaree; Nida Buawangpong; Thanachat Yotruangsri; Wichuda Jiraporncharoen; Kanokporn Pinyopornpanish (Journal of Primary Care & Community Health)
Introduction: Pneumonia is a leading cause of mortality worldwide, with Streptococcus pneumoniae being the most common cause. Older adults are particularly at risk. However, vaccination rates in Thailand remain low. Objective: This study aims to examine the prevalence of vaccine refusal and its association with factors outlined in the 5C model (Confidence, Complacency, Constraints, Calculation, and Collective Responsibility) among older patients with morbidities. Setting: Study was conducted at outpatient clinic of the Department of Family Medicine, Chiang Mai University. Methods: An observational cross-sectional study. The data was collected via a self-administered questionnaire including demographic data, questionnaire in 5C model, and intention to received pneumococcal vaccine. Comparison of characteristic between vaccine refuser and non-refuser was performed by using Chi-square or a T -test. To explore the association between factors in 5C model and vaccine refusal, multiple logistic regression was performed with an adjustment for confounders. Results: From a total of 150 participants, the mean age was 69.8 ± 5.6 years old. Most of the patients were female (60.7%). The study found that 18% of the participants refused the pneumococcal vaccine. After adjusted for the confounders, the lower collective responsibility and confidence were significantly associated with vaccine refusal (Odds ratio 0.22 (95% confidence interval [CI] 0.06-0.74, P  = .015) and Odds ratio 0.43 (95% CI 0.20-0.89, P  = .024), respectively. Conclusion: Strategies to enhance confidence and address complacency about vaccines are essential for improving pneumococcal vaccination coverage. This insight can be used as a guideline and policies can be formulated which are aimed at reducing pneumococcal vaccine refusal in the older adults by enhancing communication about the benefits, efficacy, and risks of vaccines.